Investigação dos efeitos do etanol no desempenho de inibidores cinéticos de hidratos - Renato, Bruno dos Santos (2017)
Among the main techniquesto avoid the hydratesformationis the use of thermodynamicandkinetic inhibitors and also anti-agglomerate agents. Thermodynamic inhibitors are widely used in industry. The most common in the world are monoeethyleneglycol (MEG) and methanol, already in Brazil, ethanol is the most used. Kinetic inhibitors are still rare because they have performance-related drawbacks under severe temperature and pressure conditions. Aiming to study a combined inhibition strategy between kinetics and thermodynamics using ethanol as a thermodynamic inhibitor, three different commercial kinetic inhibitors were tested under subcooling conditions in which uniquely kinetic inhibition did not yield satisfactory results. The tests were carried out in a high pressure and constant volume reactor. Hydrate formation was identified by reducing the pressure and raising the temperature of the reactor, since the formation of these crystals consumes gas is exothermic. The performance of the inhibitors was associated with the induction and crystallization times, as well as the pressure, temperature and electric current curves of the magnetic stirrer. In the experiments, a significant increase in induction time was identified for two of the kinetic inhibitors combined with ethanol in the proportion 10% by mass, and the combination with 30% of ethanolshowed a worsening in the performance relation with the subcooling. The characteristics of the hydrates formed were also altered in the presence of kinetic inhibitors and ethanol, reducing the ability of the hydrate crystals to adhere and cause blockage in pipes